Evaluation of the seismic response of masonry buildings based on energy functions. - Benedetti, D. (Earthquake engineering & structural dynamics.)
This work is based on energies evaluated from the responses of 12 stone and brick masonry systems subjected to 58 shaking table tests. The evolution of input energy during a damaging base excitation is correlated to the change of the damage patterns of the considered buildings. The comparison among energies dissipated and absorbed by the buildings during the various shocks gives some hints on strengthening strategies. It is found that damage to spandrel beams produces a more significant energy absorption than other types of damage.